2013
DOI: 10.1038/mt.2013.61
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Broad Cytotoxic T Cells by Protective DNA Vaccination Against Marburg and Ebola

Abstract: Marburg and Ebola hemorrhagic fevers have been described as the most virulent viral diseases known to man due to associative lethality rates of up to 90%. Death can occur within days to weeks of exposure and there is currently no licensed vaccine or therapeutic. Recent evidence suggests an important role for antiviral T cells in conferring protection, but little detailed analysis of this response as driven by a protective vaccine has been reported. We developed a synthetic polyvalent-filovirus DNA vaccine agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 47 publications
(85 reference statements)
0
65
0
Order By: Relevance
“…We have recently reported that highly optimized DNA vaccination with adaptive electroporation (EP) can elicit a strong Th1 and CD8 T cells, cellular immunity necessary to prevent diseae after exposure with Mtb, 28,[35][36][37][38][39] thus suggesting it as a promising platform for the development of a TB vaccine. Although a few studies have shown that EP can enhance immune responses to a DNA TB vaccine, [40][41][42] no current studies have tested this improved optimized DNA platform in the TB animal model.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have recently reported that highly optimized DNA vaccination with adaptive electroporation (EP) can elicit a strong Th1 and CD8 T cells, cellular immunity necessary to prevent diseae after exposure with Mtb, 28,[35][36][37][38][39] thus suggesting it as a promising platform for the development of a TB vaccine. Although a few studies have shown that EP can enhance immune responses to a DNA TB vaccine, [40][41][42] no current studies have tested this improved optimized DNA platform in the TB animal model.…”
Section: Discussionmentioning
confidence: 99%
“…28 Negative control mice received 3 equivalent doses of pVAX, and positive control mice were vaccinated subcutaneously with a single dose of 10 6 CFU BCG Statens Serum Institut (SSI) as previously described. 9 The BCG SSI was provided by Aeras.…”
Section: Transfection and Immunoblottingmentioning
confidence: 99%
See 2 more Smart Citations
“…These are generated through a conjugation between DCs and tumor antigens for the purpose of activating the specific anti-tumor immune response. In addition, the potentiation of immune cell activity by co-incubation of DCs with other immune cells facilitates tumor toxicity (Shedlock et al, 2013;Simor et al, 2013;Shi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%